P50, N100, and P200 Sensory Gating in Panic Disorder. (September 2020) - Thoma, Lars; Rentzsch, Johannes; Gaudlitz, Katharina; Tänzer, Nicole; Gallinat, Jürgen; Kathmann, Norbert; Ströhle, Andreas; Plag, Jens
Panic disorder (PD) has been linked to abnormalities in information processing. However, only little evidence has been published for sensory gating in PD. Sensory gating describes the brain's ability to exclude stimuli of low relevance from higher level information processing, thereby sustaining efficient cognitive processing. Deficits in sensory gating have been associated with various psychiatric conditions, most prominently schizophrenia. In this case-control event-related potential study, we tested 32 patients with PD and 39 healthy controls in a double click paradigm. Both groups were compared with regard to pre-attentive (P50), early-attentive (N100), and late-attentive (P200) sensory gating indices. Contrary to a hypothesized deficit, PD patients and healthy controls showed no differences in P50, N100 and P200 values. These results suggest that sensory gating seems to be functional across the pre-attentive, early-attentive, and late-attentive time span in this clinical population. Given this consistency across auditory sensory gating indices, further research aiming to clarify information processing deficits in PD should focus on other neurophysiological markers to investigate information processing deficits in PD (eg, P300, error-related negativity or mismatch negativity).